Characterization of traditional productive system with cocoa tree (Theobroma cacao L.) in Tumaco, Nariño - Preciado, Olegario; Ocampo, Clara Inés; Ballesteros Possú, William (Revista de Ciencias Agrícolas, 2011)
Productive cocoa farms were characterized in Tumaco, Narino, located in 1°49’ latitude north and 79°46’ longitude west. The structure and function were determined in six productive places.A simple random sampling, semistructured survey, participatory diagnostic,and informal meetings were applied. Furthermore, the surveys were analyzed by means of descriptive statistic with excel program. The T.cocoa productive system is diversified with several traditional agroforestry arrangements of T. cocoa associated with plantain Musa paradisiacal L., T. cocoa associated with fruit trees and woody trees and T. cocoa associated with palms, and sometimes T. cocoa in rangelands. T. cocoa average of production was 265,7 kg.ha-1 year-1, in 188 treesha-1. The creole cocoa with melon pods was the most predominant. However, 28% of T. cacao was affected by Monilophthora roreri and Crinnipellis pernicious. Finally, the pods index and seedswere 26 and 1.2 respectively. 58,5% the seed are ovoid shape whereas 67,6% of them showed violet intermediate color.